Soluble (pro)renin receptor treats metabolic syndrome in mice with diet-induced obesity via interaction with PPARγ - Wang, Fei (JCI Insight, 2020)
The therapies available for management of obesity and associated conditions are limited, because they are often directed toward an individual component of metabolic syndrome and are associated with adverse effects. Here, we report the multifaceted therapeutic potential of histidine-tagged recombinant soluble (pro)renin receptor (sPRR), termed sPRR-His, in a mouse model of diet-induced obesity (DIO). In the DIO model, 2-week administration of sPRR-His lowered body weight and remarkably improved multiple metabolic parameters in the absence of fluid retention. Conversely, inhibition of endogenous sPRR production by PF429242 induced diabetes and insulin resistance, both of which were reversed by the sPRR-His supplement. At the cellular level, sPRR-His enhanced insulin-induced increases in glucose uptake via upregulation of phosphorylated AKT and protein abundance of glucose transporter 4. Promoter and gene expression analysis revealed PRR as a direct target gene of PPARγ. Adipocyte-specific PPARγ deletion induced severe diabetes and insulin resistance associated with reduced adipose PRR expression and circulating sPRR. The sPRR-His supplement in the null mice nearly normalized blood glucose and insulin levels. Additionally, sPRR-His treatment suppressed DIO-induced renal sodium-glucose cotransporter-2 (SGLT2) expression. Overall, sPRR-His exhibits a therapeutic potential in management of metabolic syndrome via interaction with PPARγ.